Alcohol Assessment Among College Students Using Wireless Mobile Technology. - Bernhardt, Jay M.; Usdan, Stuart; Mays, Darren; Martin, Ryan; Cremeens, Jennifer; Arriola, Kimberly Jacob (Journal of Studies on Alcohol & Drugs, 2009)
Objective: This study used a two-group randomized design to assess the validity of measuring self-reported alcohol consumption among college students using the Handheld Assisted Network Diary (HAND), a daily diary assessment administered using wireless mobile devices. Method: A convenience sample of college students was recruited at a large, public university in the southeastern United States and randomized into two groups. A randomly assigned group of 86 students completed the daily HAND assessment during the 30-day study and a Timeline Followback (TLFB) at 30-day follow-up. A randomly assigned group of 82 students completed the paper-and-pencil Daily Social Diary (DSD) over the same study period. Data from the daily HAND assessment were compared with the TLFB completed at follow-up by participants who completed the HAND using 95% limits of agreement analysis. Furthermore, individual growth models were used to examine differences between the HAND and DSD by comparing the total drinks, drinking days, and drinks per drinking day captured by the two assessments over the study period. Results: Results suggest that the HAND captured similar levels of alcohol use compared with the TLFB completed at follow-up by the same participants. In addition, comparisons of the two study groups suggest that, controlling for baseline alcohol use and demographics, the HAND assessment captured similar levels of total drinks, drinking days, and drinks per drinking day as the paper-and-pencil DSD. Conclusions: The study findings support the validity of wireless mobile devices as a daily assessment of alcohol use among college students. (J. Stud. Alcohol Drugs 70: 711-775, 2009) Reprinted by permission of the publisher.